Anglikanizm i odrodzenie katolicyzmu na tle sytuacji religijnej w XIX-wiecznej Anglii - Kantyka, Przemysław (Studia Europaea Gnesnensia, 2016)
The article describes the religious situation in the 19th-century England with special emphasis on the position of Anglicanism and Catholicism. First, it examines the situation of the Church of England with its rise of the Oxford Movement and transformation of Anglicanism into a worldwide community. Subsequently, the paper describes the renaissance of Catholicism in the new circumstances following the enactment of Catholic Emancipation Bill . Finally, it mentions the first attempts at a dialogue between Anglicans and Catholics. All these historical developments are shown in the context of life and conversion of John Henry Newman.